2013
DOI: 10.1371/journal.pone.0080802
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Factors Associated with Severity and Fatality among Patients with Severe Fever with Thrombocytopenia Syndrome Bunyavirus Infection in Northeast China

Abstract: BackgroundIn 2009, severe fever with thrombocytopenia syndrome virus (SFTSV) was identified as a novel member of the genus phlebovirus in the Bunyaviridae family in China. The detailed clinical features of cases with SFTSV infection have not been well described, and the risk factors for severity among patients and fatality among severe patients remain to be determined.Methodology/Principal FindingsClinical and laboratory features of 115 hospitalized patients with SFTSV infection during the period from June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
165
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(191 citation statements)
references
References 33 publications
18
165
8
Order By: Relevance
“…Li et al also reported that the PLT counts between both cases were very similar [9]. On the other hand, a study in northeast China showed that the lowest PLT count on admission or throughout hospitalization was associated with the severity of SFTS [11]. In the present case, his PLT count decreased to the lowest value of 41,000/μL on the eighth day, and, thus, he did not need a PLT transfusion.…”
Section: Discussionsupporting
confidence: 63%
“…Li et al also reported that the PLT counts between both cases were very similar [9]. On the other hand, a study in northeast China showed that the lowest PLT count on admission or throughout hospitalization was associated with the severity of SFTS [11]. In the present case, his PLT count decreased to the lowest value of 41,000/μL on the eighth day, and, thus, he did not need a PLT transfusion.…”
Section: Discussionsupporting
confidence: 63%
“…The liver plays a central role in the pathogenesis of SFTSV infection (1, 3). An elevation in liver markers (AST, ALT, and LDH) was observed in five of six cases as found in a majority of SFTS patients (8), and abnormalities were observed in the laboratory tests in four of six cases (including the present case) with regards to coagulopathy, prothrombin time, activated partial thromboplastin time, fibrin/fibrinogen degradation products, fibrinogen, and/or D-dimer, all of which could reflect underlying disseminated intravascular coagulation (DIC). In four of five cases, including the present case, for which a bone marrow examination was performed, hemophagocytosis was observed, and the serum ferritin level was elevated.…”
Section: Discussionmentioning
confidence: 64%
“…By the end of 2012, 11 provinces in China have reported SFTS cases (Liu et al 2014). From 2011 to 2012, 2,047 cases were reported, among which 129 died with an average case-fatality ratio of 7.3% (Deng et al 2013). The condition of patients with critical SFTS may proceed quickly and end in multi-organ failure and death.…”
Section: Introductionmentioning
confidence: 99%